Environmentally Benign Partially Delignified and Microwave Processed Bamboo-Based Drinking Straws - Rai R.; Ranjan R.; Kant C.; Ghosh U.U.; Dhar P. (My University, 2025)
Single-use plastic straws are a significant environmental concern as they pollute the ecosystem and drastically harm humans and aquatic organisms. Paper straws, as an alternative have limitations such as weak mechanical properties, poor water stability, and the use of coatings or adhesives that hinder their biodegradability. The present study reports a facile approach for preparing mechanically robust, water-stable, and biodegradable straws using partially delignified and microwave (MW) treated bamboo. The MW-processed bamboo-based straws present water stability for up to 16 h and a contact angle of 87.8°, suggesting low wettability and water stability for long periods. The processed straws show improved tensile strength of 59.3 MPa, Young's modulus of 988 MPa, and a flexural strength of 13.9 MPa, along with >97% biodegradation (98 days). MW treatment is a rapid and low-cost strategy for physiochemical modification that can be used for the large-scale production of drinking straws from biomass. The life cycle analysis (LCA) shows that MW-irradiated bamboo straws generate 86.53% less global warming potential (GWP) impact during production and 91.8% less human health damage impact during end-of-life (EOL), compared to plastic straws. MW-treated drinking straws from bamboo can thus become a low-cost, eco-friendly, biodegradable, and sustainable alternative to paper and plastic straws. © 2023 Wiley-VCH GmbH.